The Effect of Price, Product, Promotion Towards Consumers’ Purchase Intention at T4U Indonesia, West Surabaya Branch - valentina sutanto, gracia; Gunawan, Lenny (Jurnal Entrepreneur dan Entrepreneurship, 2023)
As Food and Beverage industry growth is still claimed as the one of the highest growth potential, many retailers offer food and beverage in many forms. By observing this opportunity, Entrepreneurs are motivated in starting F&B businesses. With the COVID-19 impacting sales figures in most business specially involving dine-in activities, the researcher would like to investigate further how price, product, promotion influences the purchase intention in T4U Taiwanese beverage branch in West Surabaya. The researcher uses three variables based on the consumers’ survey result which are Price, Promotion, and Product. The purpose of this research is to know the significance level all of those variables have effect towards the consumers’ purchase intention at T4U Surabaya. The total samples are 112 respondents taken from the population people who know T4U is unknown, thus sample number is decided based on Lemeshow method. The responses are collected through questionnaire and selected with purposive sampling method then, run using SPSS. The Multiple Regression Analysis is used to analyze the data of the respondents and the result is Price, Promotion, and Product have positive and significant effect towards Consumers’ Purchase Intention at T4U Surabaya.